2021
DOI: 10.1016/j.isci.2021.102998
|View full text |Cite
|
Sign up to set email alerts
|

Emerging bioelectrochemical technologies for biogas production and upgrading in cascading circular bioenergy systems

Abstract: Biomethane is suggested as an advanced biofuel for the hard-to-abate sectors such as heavy transport. However, future systems that optimize the resource and production of biomethane have yet to be definitively defined. This paper assesses the opportunity of integrating anaerobic digestion (AD) with three emerging bioelectrochemical technologies in a circular cascading bioeconomy, including for power-to-gas AD (P2G-AD), microbial electrolysis cell AD (MEC-AD), and AD microbial electrosynthesis (AD-MES). The mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 125 publications
(171 reference statements)
0
9
0
Order By: Relevance
“…Electromethanogenesis [1,2], consisting of the reduction of CO2 in the form of methane (CH4) via microbial electrolysis [3][4], is a valuable alternative to both biochemical methanogenesis and thermochemical methanation from the Sabatier process [5][6]. Among the innovative technologies for energy conversion, the peculiarity of this bioelectrochemical process is to address the need of storing the energy produced from unprogrammable sources in renewable fuel (hydrogen or methane), in a power-to-gas concept (BEP2G) [1,[5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Electromethanogenesis [1,2], consisting of the reduction of CO2 in the form of methane (CH4) via microbial electrolysis [3][4], is a valuable alternative to both biochemical methanogenesis and thermochemical methanation from the Sabatier process [5][6]. Among the innovative technologies for energy conversion, the peculiarity of this bioelectrochemical process is to address the need of storing the energy produced from unprogrammable sources in renewable fuel (hydrogen or methane), in a power-to-gas concept (BEP2G) [1,[5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Electromethanogenesis [1,2], consisting of the reduction of CO2 in the form of methane (CH4) via microbial electrolysis [3][4], is a valuable alternative to both biochemical methanogenesis and thermochemical methanation from the Sabatier process [5][6]. Among the innovative technologies for energy conversion, the peculiarity of this bioelectrochemical process is to address the need of storing the energy produced from unprogrammable sources in renewable fuel (hydrogen or methane), in a power-to-gas concept (BEP2G) [1,[5][6][7][8][9]. Although such processes address marginal energy resources, their study finds valuable meaning in promoting a green circular economy by producing new biomethane or upgrading biomethane and CO2 from anaerobic digestion (AD) in the already operating biogas plants [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Microbial electrosynthesis cells can provide comprehensive solutions for wastewater-energy-chemicals nexus by extracting the wastewater energy and efficiently converting it into various value-added chemicals (Harnisch and Schroder, 2010;Zou and He, 2018). In particular, the integration of microbial electrosynthesis cells with MFCs has accomplished the wastewater-powered production of different commodities, such as biomethane (Ning et al, 2021), acetic acid (Nevin et al, 2010), butanol (Zaybak et al, 2013), and hexanol (Vassilev et al, 2018), thereby opening the window for bringing value to wastewater treatment (Christodoulou et al, 2017;Jiang and Zeng, 2018). A study on microbial electrosynthesis reported that in situ electrode potential modulation and control can be achieved through the introduction of additional '''pin''' electrodes (Gajda et al, 2021).…”
Section: Introductionmentioning
confidence: 99%